Culturing partial-denitrification (PD) granules in continuous flow reactor with waste sludge as inoculum performance, granular sludge characteristics and microbial community - Tao, Youqi (Environmental technology, 2024)
Partial denitrification granular sludge (PDGS) can provide long-term stable nitrite for anaerobic ammonia oxidation (anammox). The cultivation of ordinary activated sludge from wastewater treatment plants into PDGS can further promote the application of PD in practical engineering. In this study, the feasibility of fast start-up of PDGS was explored by inoculating waste sludge in up-flow anaerobic sludge blanket (UASB) reactor with synergistic control of nitrogen load rate (NLR, 0.05-0.65 kg N/m3/d) and electron donor starvation (EDS) (240-168 mg L-1), and system performance, particle characteristics and microbial structure were studied. The results showed that PD-UASB started successfully within 48 days, the average nitrite accumulation rate (NTR) and nitrate removal ratio (NRR) reached 79.6% and 82.5% after successful initiation, accompanied by high abundance of PD bacteria (Thauera, Pseudomonas, unclassflied commamonadaceae and Limnobacter) (25.3%). The increase of PD activity, and the difference between nitrate reductase (NAR) and nitrite reductase (NIR) contributed to nitrite production. Besides, the sludge shifted from flocculated (≤0.5 mm, 95.37%) to granulated state (0.5-2 mm, 64.74%), which could be due to the increase of extracellular polymers (EPS) (especially T-EPS) and metabolism of specific microorganisms (Bacteroidota and Chloroflexi, 19.92%). Good sludge granulation promoted the settleability of PD (the SVI5 was 47.248 mL/ g. ss after successful start-up). In summary, good PD sludge granulation process could be achieved in a short time by synergistically controlling NLR and EDS